Women, rites, and ritual objects in premodern Japan - Gerhart, Karen M. (Brill's Japanese studies library, 2018)
Front Matter -- Copyright Page -- Prologue -- List of Contributors -- Introduction -- Rituals Related to the Household and Childbirth -- Women and “Moving House” Rituals in Mid-Heian Japan -- Devising the Esoteric Rituals for Women: Fertility and the Demon Mother in the Gushi nintai sanshō himitsu hōshū by Anna Andreeva -- Taira no Tokushi’s Birth of Emperor Antoku by Naoko Gunji -- Women and Buddhist Rituals and Icons -- A Female Deity as the Focus of a Buddhist Ritual: Kichijō Keka at Hōryūji by Chari Pradel -- The Relic and the Jewel: An Eleventh-Century Miniature Bronze Pagoda to Hold the Bones of a Young Queen by Hank Glassman -- Connecting Kannon to Women Through Print by Sherry Fowler -- Buddhist Women and Death Memorials -- Commemorating Life and Death: The Memorial Culture Surrounding the Rinzai Zen Nun Mugai Nyodai by Patricia Fister -- Of Surplices and Certificates: Tracing Mugai Nyodai’s Kesa by Monica Bethe -- Female Patronage, Portraits, and Rituals -- Retired Empress and Buddhist Patron: Higashisanjō-in Donates a Set of Icon Curtains in the Illustrated Legends of Ishiyamadera Handscroll by Elizabeth Morrissey -- Life After Death: The Intersection of Patron and Subject in the Portrait of Jōkō-in by Elizabeth Self -- Back Matter -- Index.